2009
DOI: 10.5055/ajdm.2009.0022
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric disaster preparedness in the medical setting: Integrating mental health

Abstract: Introduction: The increasing prevalence of disasters worldwide highlights the need for established and universal disaster preparedness plans.The devastating events of September 11 and Hurricane Katrina have spurred the development of some disaster response systems. These systems, however, are predominantly focused on medical needs and largely overlook mental health considerations. Negative outcomes of disasters include physical damage as well as psychological harm. Mental health needs should be considered thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Children are particularly vulnerable in disasters, as they have a range of psychological and physical reactions to trauma and disaster situations that are more subtle compared with older victims. [3][4][5] Pediatric disaster victims are challenging for hospital personnel, who may be unfamiliar with the care of the pediatric patient 5,6 and with pediatric disaster triage (PDT). The use of PDT tools and formal training of all HPs who may be involved in resource allocation decisions therefore becomes crucial.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Children are particularly vulnerable in disasters, as they have a range of psychological and physical reactions to trauma and disaster situations that are more subtle compared with older victims. [3][4][5] Pediatric disaster victims are challenging for hospital personnel, who may be unfamiliar with the care of the pediatric patient 5,6 and with pediatric disaster triage (PDT). The use of PDT tools and formal training of all HPs who may be involved in resource allocation decisions therefore becomes crucial.…”
mentioning
confidence: 99%
“…This ultimately eliminates the need for an instructor. 17 Screen-based simulation eliminates interprofessional training barriers as it is highly replicable, has a relatively low cost of implementation, 13 allows for a standardized collection of performance data and offers scalability, [1][2][3][4][5][6][7][8][9]18 and is preferred since the beginning of COVID-19 pandemic as it promotes social distanciation. 19 Previous investigators suggested the use of serious games, a type of SBS, to recalibrate physician heuristics by reducing physicians' undertriage [20][21][22][23] in the context of MCIs.…”
mentioning
confidence: 99%
See 1 more Smart Citation